Tracking eye gaze during interpretation of endoluminal three-dimensional CT colonography: visual perception of experienced and inexperienced readers. - Mallett, S; Phillips, P; Fanshawe, T; Helbren, E; Boone, D; Gale, A; Taylor, SA; Manning, D; Altman, D; Halligan, S (Radiological Society of North America Inc., 2014)
PURPOSE: To identify and compare key stages of the visual process in experienced and inexperienced readers and to examine how these processes are used to search a moving three-dimensional ( 3D three-dimensional ) image and their relationship to false-negative errors. MATERIALS AND METHODS: Institutional review board research ethics approval was granted to use anonymized computed tomographic (CT) colonographic data from previous studies and to obtain eye-tracking data from volunteers. Sixty-five radiologists (27 experienced, 38 inexperienced) interpreted 23 endoluminal 3D three-dimensional CT colonographic videos. Eye movements were recorded by using eye tracking with a desk-mounted tracker. Readers indicated when they saw a polyp by clicking a computer mouse. Polyp location and boundary on each video frame were quantified and gaze data were related to the polyp boundary for each individual reader and case. Predefined metrics were quantified and used to describe and compare visual search patterns between experienced and inexperienced readers by using multilevel modeling. RESULTS: Time to first pursuit was significantly shorter in experienced readers (hazard ratio, 1.22 [95% confidence interval: 1.04, 1.44]; P = .017) but other metrics were not significantly different. Regardless of expertise, metrics such as assessment, identification period, and pursuit times were extended in videos where polyps were visible on screen for longer periods of time. In 97% (760 of 787) of observations, readers correctly pursued polyps. CONCLUSION: Experienced readers had shorter time to first eye pursuit, but many other characteristics of eye tracking were similar between experienced and inexperienced readers. Readers pursued polyps in 97% of observations, which indicated that errors during interpretation of 3D three-dimensional CT colonography in this study occurred in either the discovery or the recognition phase, but rarely in the scanning phase of radiologic image inspection.